Problems with Regional Head Elections: Constitutional Court Decisions on Disputes over Regional Head Election Results in Jambi Province - Windi Aji , Ari Bakti; Repelita, Repelita; Kasmarani, Yuli; Tri Yandy, Eza; Rahmat , Al Fauzi (Al-Risalah, 2023)
This research is entitled Problems of Regional Head Elections (Study of Constitutional Court Decisions regarding Disputes over Regional Head Election Results in Jambi Province). This type of research is normative legal research. The focus of the research is to examine what are the legal issues for regional head elections submitted by the Petitioners in cases of regional head election results in the Jambi province region to the Constitutional Court and how the trend of decisions based on legal considerations of the Constitutional Court in cases of regional head election disputes in the Jambi province region. The results of the study show that the legal issues raised by the Petitioners in the case of disputes over the results of regional head elections to the Supreme Court of the Constitution are quite numerous and varied, some are proven, and some were not proven because the Court did not believe in the evidence presented by the Petitioners, and some were not proven because the Court had not considered them. These problems in general include: administrative violations, legal violations in the form of money politics, intimidation and mobilization of civil servants, village heads, and village officials by the incumbent regional head candidate. The organizers allow violations and side with one pair of candidates. As for the issue of decision trends, the majority of applications were rejected and could not be accepted, while for requests that were and there were only 2 (two) cases, namely the 2013 Election of the Regent and Deputy Regent of Kerinci district and the 2020 Election of the Governor and Deputy Governor of Jambi province. Then, there are different trends in MK decisions, Niet Ontvankelijke Verklaard), and focus more on the formal requirements of the application which often overrides the substance of the case.